A narrative review on sacubitril/valsartan and ventricular arrhythmias. Issue 27 (8th July 2022) - Wei, Zhaoyang; Zhang, Meiwei; Zhang, Qian; Gong, Linan; Wang, Xiangyu; Wang, Zanzan; Gao, Ming; Zhang, Zhiguo
Abstract : Sacubitril/valsartan, the first angiotensin receptor neprilysin inhibitor approved by the Food and Drug Administration for marketing, has been shown to reduce the risk of cardiovascular death or heart failure hospitalization and improve symptoms in patients with chronic heart failure with a reduced ejection fraction. However, some researchers have also found that sacubitril/valsartan has an antiarrhythmic effect. The mechanism by which sacubitril/valsartan reduces the mortality associated with malignant ventricular arrhythmias is not precise. Many studies have concluded that ventricular arrhythmia is associated with a reduction in myocardial fibrosis. This article reviews the current understanding of the effects of sacubitril/valsartan on the reduction of ventricular arrhythmia and explains its possible mechanisms. The results of this study suggest that sacubitril/valsartan reduces the occurrence of appropriate implantable cardioverter-defibrillator shocks. Meanwhile, sacubitril/valsartan may reduce the occurrence of ventricular arrhythmias by affecting 3 pathways of B-type natriuretic peptide, Angiotensin II, and Bradykinin. The conclusion of this study is that sacubitril/valsartan reduces the number of implantable cardioverter-defibrillator shocks and ventricular arrhythmias in heart failure with reduced ejection fraction patients.